2020
DOI: 10.1186/s13578-020-00488-y
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cancer-associated fibroblasts as emerging targets for hepatocellular carcinoma

Abstract: The tumor microenvironment (TME) is a complex multicellular functional compartment that includes fibroblasts, myofibroblasts, endothelial cells, immune cells, and extracellular matrix (ECM) elements. The microenvironment provides an optimum condition for the initiation, growth, and dissemination of hepatocellular carcinoma (HCC). As one of the critical and abundant components in tumor microenvironment, cancer-associated fibroblasts (CAFs) have been implicated in the progression of HCC. Through secreting variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 134 publications
0
50
0
Order By: Relevance
“…The tumor microenvironment (TME) is a sophisticated organizational structure that refers to the intracellular milieu produced by tumor cells and required for tumor cells to survive, including fibroblasts, tumor cells, inflammatory and immune cells and other types of cells around them, as well as intercellular stroma, extracellular matrix (ECM), microvessels and signaling biomolecules in nearby areas [ 9 ]. Tumor development and progression are affected by changes in the TME, which is produced by the dynamic interaction between malignant cells and normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor microenvironment (TME) is a sophisticated organizational structure that refers to the intracellular milieu produced by tumor cells and required for tumor cells to survive, including fibroblasts, tumor cells, inflammatory and immune cells and other types of cells around them, as well as intercellular stroma, extracellular matrix (ECM), microvessels and signaling biomolecules in nearby areas [ 9 ]. Tumor development and progression are affected by changes in the TME, which is produced by the dynamic interaction between malignant cells and normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although epithelial cell signaling in Helicobacter pylori infection and oocyte meiosis are not associated with HCC progression, evidence suggests that TLR is involved in modulating the previous pathways ( Smith et al, 2011 ; Gilbert, 2019 ). The tumor microenvironment including fibroblasts, myofibroblasts, endothelial cells, immune cells, and extracellular matrix plays a critical role in the initiation, growth, and dissemination of HCC ( Zhang et al, 2020 ). Here, we observed that high RS was characterized by a high immune score, immune checkpoint expression, and immune cell infiltration in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The main pathological type of NPC is squamous cell carcinoma, but cell cycle genes have been reported to affect the differentiation of squamous cells 25,26 . ECM-related genes play an indispensable role in the tumor microenvironment, and their potential as target genes and biomarkers has been described in many studies 27 . The susceptibility to NPC in the Chinese population is closely related to the interleukin (IL)-13 gene 28 , while IL-4 has been shown to affect the progression of NPC by affecting the signal transducer and activator of transcription (STAT) pathway 29 .…”
Section: Discussionmentioning
confidence: 99%